Diversity-Oriented Synthesis of 2,4,6-Trisubstituted Piperidines via Type II Anion Relay Chemistry (ARC) - Smith, Amos B. (2011)
[Image: see text] An effective, general protocol for the Diversity-Oriented Synthesis (DOS) of 2,4,6-trisubstituted piperidine congeners has been designed and validated. The successful strategy entails a modular approach to all possible stereoisomers of the selected piperidine scaffold, exploiting Type II Anion Relay Chemistry (ARC), followed in turn by intramolecular S(N)2 cyclization, chemoselective removal of the dithiane moieties and carbonyl reductions.